The impact and challenges of the 2018 MHRA statement on the use of sodium valproate in women of childbearing age during the first year of implementation, in a UK epilepsy centre. (July 2020) - Davies, Philippa; Reuber, Markus; Grunewald, Richard; Howell, Stephen; Dickson, Jon; Dennis, Gary; Shanmugarajah, Priya; Tsironis, Theocharis; Brockington, Alice
Highlights: Use of sodium valproate in pregnancy can cause neurodevelopmental disorders and birth defects. Regulations to restrict its use in women of childbearing age were introduced in the UK in April 2018. This study evaluated the application of these MHRA regulations in the first year after introduction. In over half of cases, MHRA regulations were not applied in full to women taking sodium valproate. This was most often due to the presence of severe learning disability or simple patient choice. Abstract: Purpose: On 24/04/2018, the United Kingdom (UK) Medicines and Healthcare Products Regulatory Agency (MHRA) clarified previous policies by issuing a statement, that the use of sodium valproate is contraindicated in women of childbearing potential unless the conditions of a pregnancy prevention programme are met, and only if other treatments are ineffective or not tolerated. We evaluated the impact of this over the first year of implementation in a tertiary epilepsy centre. Methods: Cross-sectional study of all women under active follow up, or newly referred, of childbearing age (16–55 years), taking valproate for the treatment of epilepsy, over 12 months from 01/05/2018. Results: We identified 125 cases, with 31 newly referred in response to MHRA regulations. 9.6% of patients did not attend their appointment, 35.2% had a learning disability (LD), which in 19.2% was sufficiently severe that they could not consent to a sexual relationship. Patients with LD prescribed valproate were significantly younger, and more likely to have a focal or uncharacterised epilepsy than patients without LD. In 46.4% of patients, MHRA regulations were followed: women were already using highly active contraception (HAC), HAC was started, or valproate withdrawn. In 24.8% of cases, women elected to continue valproate, and were not willing to use HAC. Conclusions: In 53.6% of cases, MHRA regulations contraindicating the use valproate in women of childbearing potential could not be followed fully, due to lack of patient attendance, lack of applicability in severe LD, or ethical concerns relating to patient choice.